How does Happiness at Work Affect Employee Performance in the Head Office of BKKBN? - Endah Agustien; Pantius Drahen Soeling (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2020)
This study aims to determine the extent of the role of happiness at work in improving employee performance in the head office of BKKBN, both directly and indirectly. The approach of research uses quantitative methods. Primary data were collected by distributing questionnaires. Analysis of data processed by descriptive analysis and inferential analysis using the Structural Equation Model through SmartPLS software to 200 respondents data. The results showed that happiness at work had not directly effect employee performance, but when the relationship was mediated by work motivation there was a positive and significant effect between happiness at work on employee performance.